An overview of microwave hydrothermal carbonization and microwave pyrolysis of biomass - Nizamuddin, S.; Baloch, H.; Siddiqui, M.; Mujawar, Mubarak; Tunio, M.; Bhutto, A.; Jatoi, A.; Griffin, G.; Srinivasan, M. (2018)
© 2018, Springer Nature B.V. Biomass utilization has received much attention for production of high density solid fuels. Utilization of cheap and naturally available precursors through environmentally friendly and effective processes is an attractive and emerging research area. Pyrolysis and hydrothermal carbonization (HTC) are well-known technologies available for production of solid biofuel using conventional or microwave heating. Microwave heating is a simpler and more efficient heating method than conventional heating. This study presents a critical review on microwave pyrolysis and microwave HTC for solid fuel production in terms of yield and quality of products. Moreover, a brief summary of parameters of microwave pyrolysis and microwave HTC are discussed. The fuel, chemical, structural and thermal weight loss characteristics of solid fuels produced from different biomass are discussed and compared.